Epidemiology and antimicrobial resistance of methicillin-resistant Staphylococcus aureus isolates colonizing pigs with different exposure to antibiotics - Lopes, Elizeth (2020)
Background In 2016, very high rates of methicillin-resistant Staphylococcus aureus (MRSA)-ST398 (99%) were found in Portuguese pig farms that used colistin, amoxicillin, and zinc oxide as feed additives. Since then, farms A and B banned the use of colistin, and farm C banned the use of both antibiotics. Objective The aim of the present study was to evaluate the impact of the ban of colistin and amoxicillin on pig MRSA carriage rates, clonal types and antimicrobial resistance, compared to the results obtained in 2016. Methods In 2018, 103 pigs (52 from farm B using amoxicillin only as a feed additive and 51 from farm C where no antibiotics were included in the feed regimen) were nasally swabbed for MRSA colonization. Isolates were tested for antimicrobial susceptibility, and characterised by spa typing, SCCmec typing and MLST. Whole genome sequencing (WGS) was performed for representative isolates. Results Overall, 96% of the pigs swabbed in 2018 carried MRSA, mostly ST398-SCCmec V-spa types t011/t108. MRSA from pigs not receiving antibiotics in the feed regimen showed susceptibility to a higher number of antibiotics, namely erythromycin, ciprofloxacin, gentamicin, and chloramphenicol. Notably, most of these isolates (n = 52) presented an unusual erythromycin-susceptibility/clindamycin-resistance phenotype. WGS showed that these isolates lacked the erm and the lnu genes encoding resistance to macrolides and lincosamides, respectively, but carried the vgaALC gene encoding resistance to lincosamides, which is here firstly identified in S. aureus ST398. Conclusion After two years the ban of colistin and amoxicillin as feed additives had no significant impact on the MRSA nasal carriage rates. Nevertheless, the MRSA strains circulating in those farms showed resistance to a lower number of antibiotic classes.